2014
DOI: 10.1111/bij.12345
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance of sexually dichromatic UV-blue patches varies during the breeding season and between two subspecies ofGallotia galloti(Squamata: Lacertidae)

Abstract: Body coloration is sexually dimorphic in many vertebrate species, including lizards, in which males are often more conspicuous than females. A detailed analysis of the relative size of coloured patches and their reflectance, including the ultraviolet (UV) range, has rarely been performed. In the present work we quantified sexual dimorphism in body traits and surface area of all lateral patches from adult females and males of two subspecies of Gallotia galloti (G. g. galloti and G. g. eisentrauti). We also anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…These lizards inhabit different islands of the Canary Achipelago: Tenerife Island ( G. g. eisentrauti and G. g. galloti ), La Palma Island ( G. g. palmae ), and the small islets of Roque de Anaga ( G. g. insulanagae ). In addition, while G. g. eisentrauti and G. g. palmae inhabit cloudy and wet densely vegetated forest areas in northern Tenerife and La Palma respectively, G. g. galloti lives in dry and sunny semidesert areas in the south and the center of Tenerife ( Thorpe & Brown, 1989 ; Bohórquez-Alonso & Molina-Borja, 2014 ). Hence, the divergent ecological conditions of each area might modulate the expression of chemical signals, as it has been described for visual ornaments ( Thorpe & Brown, 1989 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These lizards inhabit different islands of the Canary Achipelago: Tenerife Island ( G. g. eisentrauti and G. g. galloti ), La Palma Island ( G. g. palmae ), and the small islets of Roque de Anaga ( G. g. insulanagae ). In addition, while G. g. eisentrauti and G. g. palmae inhabit cloudy and wet densely vegetated forest areas in northern Tenerife and La Palma respectively, G. g. galloti lives in dry and sunny semidesert areas in the south and the center of Tenerife ( Thorpe & Brown, 1989 ; Bohórquez-Alonso & Molina-Borja, 2014 ). Hence, the divergent ecological conditions of each area might modulate the expression of chemical signals, as it has been described for visual ornaments ( Thorpe & Brown, 1989 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that these two compounds might have protective properties under different environmental conditions; cholesterol might protect semiochemicals in dry conditions and vitamin E in wet environments ( Escobar et al, 2003 ; Weldon, Flachsbarth & Schulz, 2008 ; Martín & López, 2014 ). Since the environment varies considerably among subspecies ( Thorpe & Brown, 1989 ; Bohórquez-Alonso & Molina-Borja, 2014 ), this could translate into different abundances of both compounds. Moreover, as this lizard species is active during the whole year, we also examined whether the femoral gland secretions differed between the reproductive and the non-reproductive seasons.…”
Section: Introductionmentioning
confidence: 99%
“…No evidence of similar patterns are still available for the ruin lizard, thus further studies are needed to investigate the real role of the species polychromatism (Corti et al ., ). Interestingly, in other territorial not polymorphic species, it has been found that, for instance, chromatic patches may function as status signalling badges of aggressiveness, fighting ability or dominance in males (Bohórquez‐Alonso & Molina‐Borja, ). In addition, it has been suggested a possible role of testosterone as modulating factor (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Colour in lizards is an important pattern in sexual recognition and both intra‐ and intersexual competition (Bohórquez‐Alonso & Molina‐Borja, ; Klomp et al ., ). Notably, brilliant colours of the back, throat and vent may determine the fighting outcome (Klomp et al ., ) by revealing male's quality and fighting ability to the opponent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation